Can better workplace communication serve to improve job satisfaction and reduce absenteeism? A case study of Nilai University College Library - Cheng, Wei Hin; Md Isa, Filzah; Bohari, Abdul Manaf (Society for Business Research Promotion, 2014)
This study examined the relationship of the workplace communication, job satisfaction and absenteeism of the student workers in the Nilai University College library.The result of the study indicates that there is no significant relationship between the three variables.Step wise regressions show that there is negative correlation between workplace communication and job satisfaction; and absenteeism. Result also shows weak correlation between job satisfaction and absenteeism.